Cyclosporine Does Not Prevent Microvascular Loss in Transplantation but Can Synergize With a Neutrophil Elastase Inhibitor, Elafin, to Maintain Graft Perfusion During Acute Rejection. Issue 7 (27th February 2015) - Jiang, X.; Nguyen, T. T.; Tian, W.; Sung, Y. K.; Yuan, K.; Qian, J.; Rajadas, J.; Sallenave, J.‐M.; Nickel, N. P.; de Jesus Perez, V.; Rabinovitch, M.; Nicolls, M. R.
<x xml:space="preserve">Abstract</x> The loss of a functional microvascular bed in rejecting solid organ transplants is correlated with fibrotic remodeling and chronic rejection; in lung allografts, this pathology is predicted by bronchoalveolar fluid neutrophilia which suggests a role for polymorphonuclear cells in microcirculatory injury. In a mouse orthotopic tracheal transplant model, cyclosporine, which primarily inhibits T cells, failed as a monotherapy for preventing microvessel rejection and graft ischemia. To target neutrophil action that may be contributing to vascular injury, we examined the effect of a neutrophil elastase inhibitor, elafin, on the microvascular health of transplant tissue. We showed that elafin monotherapy prolonged microvascular perfusion and enhanced tissue oxygenation while diminishing the infiltration of neutrophils and macrophages and decreasing tissue deposition of complement C3 and the membrane attack complex, C5b‐9. Elafin was also found to promote angiogenesis through activation of the extracellular signal‐regulated kinase (ERK) signaling pathway but was insufficient as a single agent to completely prevent tissue ischemia during acute rejection episodes. However, when combined with cyclosporine, elafin effectively preserved airway microvascular perfusion and oxygenation. The therapeutic strategy of targeting neutrophil elastase activity alongside standard immunosuppression during acute rejection episodes may be an effective approach for preventing the development of irreversible fibrotic remodeling.